PROBLEMS OF VOCATIONAL EDUCATION REFORM IN MARKET CONDITIONS - Usen S. Alimbetov; Gulmira Z. Zaynelova; Mainura A. Ordabaeva (Статистика и экономика, 2016)
The article examines the effectiveness of vocational education, which can be viewed in two ways: as a subsystem , operated bythe needs for skilled workers - the micro-level, and as a subsystemthrough which achieved saturation of the labor market competitivestaff, contributing to higher rates of growth of national income - the macro level. The latter is a new direction, displacing the center of gravity to study the problems of a single educational institution onthe analysis of the economy of the whole country, in which the activities of the educational system, on the one hand, and employment oftrained workers, on the other.